Le dieu ordonne. Remarques sur les ordres d’Asklépios dans les inscriptions de Lébèna (Crète) - Pierre Sineux (Kentron, 2004)
The stories of dreams of Hellenistic times, from Asklepios sanctuary in Lebena (Crete) – together with those which appear in the iamata written by those in charge of the sanctuary (following the models of “healing stones” in Epidaurus) and those which are integrated in dedications to the god – recurrently mention orders given by the god: orders to come to his sanctuary, orders to hold on, orders to write the story of a vision. The god’s power to command that is expressed here – and goes beyond the incubation context – actually belongs to a representation of his potency whose permanence in the history of religion should be emphasized.